The impact of business groups on green innovation: evidence from Chinese non-SOE listed companies - Peng Gao; Qian Liu; Marek Vochozka (Discover Sustainability)
Abstract This paper examines whether and how non-state-owned enterprise (non-SOE) business groups affect a firm’s green innovation. On the basis of a sample of A-share listed companies on the Shanghai and Shenzhen stock exchanges from 2007 to 2021 and hand-collected business group data, we document a negative association between non-SOE business groups and corporate green innovation. Furthermore, we identify two different mechanisms that may explain this relationship from various perspectives: firms’ motivation for benefit maximization and the ability to lighten government environmental regulations. We also find that this negative correlation is more pronounced in competitive industries and is related to reduced executives' environmental awareness, reduced intensity of environmental regulation, and greater official pressure to promote. Our findings not only help improve the existing literature on business groups and corporate green innovation but also provide empirical evidence that non-SOE business groups can negatively affect corporate green innovation.